PENGGUNAAN ARTIFICIAL INTELLIGENCE DALAM PEMBELAJARAN BAHASA JEPANG DI PERGURUAN TINGGI VOKASI - Nita Rustanti (JURNAL PENGABDIAN KEPADA MASYARAKAT (ADI DHARMA), 2025)
This study aims to explain the use of AI in Japanese language learning by students and whether there are any impacts caused by the use of AI both positive and negative. The subjects of this research are students of Office Administration Study Program and Hospitality Study Program of Pajajaran ICB Polytechnic who have taken Japanese language courses. The method used was mixed method with data collection techniques are questionnaires, interviews and literature studies. Analysis was carried out by quantitative descriptive analysis and data reduction. The results of the study explain that the types of AI used by students in the Japanese language learning process are ChatGPT, Google translate, Gemini AI, Meta AI Whatsapp and Japanese Language Application. AI is used to make sentences, read hiragana letters, have conversations, look up vocabulary, numbers and clocks. There is no significant negative or positive impact of using AI in Japanese language learning, either from the level of dependence or assistance. This is due to the infrequent use of AI by students. Keywords: Artificial Intelligence; Japanese Learning; ChatGPT